THE EFFECT OF PRESCRIBED FIRE ON THE MICROCLIMATE OF FOREST FLOOR - Yanto Sugianto; David Yates (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1992)
Abstract is available in the full text (pdf format)